Model Pembelajaran Cooperative STAD Terhadap Kemampuan Pemecahan Masalah Pada Materi Pertidaksamaan Linear 1 Variabel Kelas VIII A siswa SMP Taman Siswa Pematangsiantar - Sarah Fergy Simangunsong; Indah Safirna Indah; Junita Panjaitan; Natasya Agustina Girsang; Daulat Nathanael Banjarnahor (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to describe the influence of the Student Teams-Achievement Divisions (STAD) cooperative learning model on the mathematical problem-solving abilities of Grade VIII A students at SMP Taman Siswa Pematangsiantar, specifically on the subject of Linear Inequalities in One Variable. A quantitative approach was employed using a quasi-experimental one-group pretest-posttest design involving 30 students selected through total sampling. Data were collected via essay-based problem-solving tests, covering indicators of understanding the problem, devising a plan, carrying out the plan, and looking back to interpret the solution. The data were subsequently analyzed using descriptive statistics, paired t-tests, and normalized N-Gain calculations. The results demonstrate a significant increase in posttest scores compared to pretest scores, with the percentage of learning mastery rising from approximately 30% to 80%. The N-Gain value fell within the moderate category, with the most prominent improvements observed in the indicators of understanding the problem and devising a plan. The paired t-test yielded a significance value of < 0,05, indicating a statistically significant difference in problem-solving abilities before and after the implementation of STAD. Furthermore, observations revealed an enhancement in student activity, social interaction, and learning responsibility within group work. It is concluded that the STAD cooperative learning model contributes positively to improving students' mathematical problem-solving skills in linear inequalities and serves as a viable alternative for mathematics instruction in junior high schools.